Remote Sensing Phenology of Antarctic Green and Red Snow Algae Using WorldView Satellites - Gray, Andrew; Krolikowski, Monika; Fretwell, Peter; Convey, Peter; Peck, Lloyd S.; Mendelova, Monika; Smith, Alison G.; Davey, Matthew P. (Frontiers in Plant Science, 2021)
Snow algae are an important group of terrestrial photosynthetic organisms in Antarctica, where they mostly grow in low lying coastal snow fields. Reliable observations of Antarctic snow algae are difficult owing to the transient nature of their blooms and the logistics involved to travel and work there. Previous studies have used Sentinel 2 satellite imagery to detect and monitor snow algal blooms remotely, but were limited by the coarse spatial resolution and difficulties detecting red blooms. Here, for the first time, we use high-resolution WorldView multispectral satellite imagery to study Antarctic snow algal blooms in detail, tracking the growth of red and green blooms throughout the summer. Our remote sensing approach was developed alongside two Antarctic field seasons, where field spectroscopy was used to build a detection model capable of estimating cell density. GPS tagging of blooms and in situ life cycle analysis was used to validate and verify our model output. WorldView imagery was then used successfully to identify red and green snow algae on Anchorage Island (Ryder Bay, 67◦S), estimating peak coverage to be 9.48×10^4m2and 6.26×10^4m2, respectively. Combined, this was greater than terrestrial vegetation area coverage for the island, measured using a normalised difference vegetation index (NDVI). Green snow algae had greater cell density and average layer thickness than red blooms (6.0×10^4cells ml−1versus 4.3×10^4cells ml^−1) and so for Anchorage Island estimated that green algae dry biomass was over three times that of red algae (567 kg versus 180 kg, respectively). Thanks to the high spatial resolution of the WorldView imagery and its ability to detect red blooms, calculated snow algal area was 17.5 times greater than estimated with Sentinel 2 imagery. This highlights a scaling problem of using coarse resolution imagery and suggests snow algal contribution to net primary productivity on Antarctica may be far greater than previously recognised.